DIVORCE DUE TO DOMESTIC VIOLENCE IN SINJAI DISTRICT (Perspective Analysis of Islamic Law) - Nazaruddin, Nazaruddin; Rasdiyanah, Andi; Ridwan, Muh. Saleh; Kurniati, Kurniati (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The purpose of this study is to find out the various factors that cause divorce due to domestic violence in Sinjai Regency and to describe how to resolve divorce due to domestic violence in Sinjai Regency and to elaborate on how divorce due to domestic violence is from an Islamic legal perspective. This research is a qualitative descriptive field research, taking place in Sinjai Regency. The approach used is a normative theological approach, a juridical approach and a sociological approach. The data collection obtained in the field with the technique of observation, interviews / interviews and documentation. The collected data is then processed using data reduction analysis, data presentation and conclusion drawing. Furthermore, by linking one of the theories of Islamic law, namely the theory of existence and competence of religious courts, the process of resolving divorce cases due to domestic violence in Sinjai Regency, which in this case is the authorized and entitled institution in resolving it, namely the Sinjai level I religious court, goes through several stages. namely through table I, table II and table III. However, before the plaintiffs and defendants seek justice, the panel of judges first has the obligation to mediate/advise both parties, in which the panel of judges makes every effort to provide the best advice or solution to the plaintiff or defendant. And Islamic law does not legalize violence against wives. Beating a wife who does nusyuz as contained in QS al-Nisa` verse 34 should be interpreted as an act to teach a lesson / for obedience, not to hurt or even do violence. The beatings carried out in the case of nusyuz basically should not injure. Meanwhile, the husband's act of hitting his wife until he is injured or the husband's violence against his wife can be declared as nusyuz of the husband against his wife. Furthermore, related to divorce due to domestic violence in Sinjai Regency which is analyzed from the perspective of Islamic law, the researcher connects one of the theories of Islamic law that applies in Indonesia to date, namely the theory of existence and competence of the Sinjai religious court which refers to the compilation of Islamic law or Islamic law. KHI. al-Nisa` verse 34 should be interpreted as an act to teach a lesson/to obey, not to hurt or even do violence. The beatings carried out in the case of nusyuz are basically not allowed to injure. Meanwhile, the husband's act of hitting his wife until he is injured or the husband's violence against his wife can be declared as nusyuz of the husband against his wife. Furthermore, related to divorce due to domestic violence in Sinjai Regency which is analyzed from the perspective of Islamic law, the researcher connects one of the theories of Islamic law that applies in Indonesia to date, namely the theory of existence and competence of the Sinjai religious court which refers to the compilation of Islamic law or Islamic law. KHI. al-Nisa` verse 34 should be interpreted as an act to teach a lesson/to obey, not to hurt or even do violence. The beatings carried out in the case of nusyuz basically should not injure. Meanwhile, the husband's act of hitting his wife until he is injured or the husband's violence against his wife can be declared as the husband's nusyuz against his wife. Furthermore, related to divorce due to domestic violence in Sinjai Regency which is analyzed from the perspective of Islamic law, the researcher connects one of the theories of Islamic law that applies in Indonesia to date, namely the theory of existence and competence of the Sinjai religious court which refers to the compilation of Islamic law or Islamic law. KHI. The beatings carried out in the case of nusyuz basically should not injure. Meanwhile, the husband's act of hitting his wife until he is injured or the husband's violence against his wife can be declared as nusyuz of the husband against his wife. Furthermore, related to divorce due to domestic violence in Sinjai Regency which is analyzed from the perspective of Islamic law, the researcher connects one of the theories of Islamic law that applies in Indonesia to date, namely the theory of existence and competence of the Sinjai religious court which refers to the compilation of Islamic law or Islamic law. KHI. The beatings carried out in the case of nusyuz are basically not allowed to injure. Meanwhile, the husband's act of hitting his wife until he is injured or the husband's violence against his wife can be declared as the husband's nusyuz against his wife. Furthermore, related to divorce due to domestic violence in Sinjai Regency which is analyzed from the perspective of Islamic law, the researcher connects one of the theories of Islamic law that applies in Indonesia to date, namely the theory of existence and competence of the Sinjai religious court which refers to the compilation of Islamic law or Islamic law. KHI.